Anti-heavy metal poisoning denitration catalyst and preparation method thereof
Patent Information
- Application Number
- CN202610987960.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明的目的在于提供一种抗重金属中毒脱硝催化剂及其制备方法,该脱硝催化剂在高砷负载量下仍然具有较高的脱硝活性,能够有效抵抗重金属中毒,解决了脱硝催化剂中毒失活的问题
1、本发明以多级孔SAPO-n分子筛为牺牲模板,利用其在高碱浓度下晶体结构易坍塌、易溶解的劣势,在其表面构建TiO2-V2O5-MoO3-Sb2O3复合壳层后,通过精准的碱处理工艺将内部SAPO-n分子筛核完全脱除,最终得到具有空心结构的TiO2-V2O5-MoO3-Sb2O3脱硝催化剂。该空心结构为重金属提供了物理容纳空间,使其在壳层内表面沉积,从而有效延缓了重金属向活性位点的扩散与覆盖,避免了现有技术中因孔道堵塞或活性位点覆盖而导致的中毒失活问题,显著提升了脱硝催化剂在含重金属烟气环境下的使用寿命,该脱硝催化剂在燃煤电厂所使用的含高砷煤种中具有较高的工业价值。
Smart Images

Figure CN122999174A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flue gas denitrification catalyst preparation technology, and in particular to a denitrification catalyst resistant to heavy metal poisoning and its preparation method. Background Technology
[0002] The combustion of fossil fuels and organic waste releases nitrogen oxides (NOx). x ), sulfur oxides (SO x NO, along with pollutants such as nitrogen oxides and heavy metals, can cause environmental problems such as acid rain, smog, and photochemical smog, seriously threatening the ecological environment and human health. Selective catalytic reduction (SCR) has become the mainstream technology in the field of denitrification due to its high denitrification efficiency and mature process. This technology uses ammonia as a reducing agent to precipitate NO on the surface of a vanadium-titanium-based catalyst (represented by V2O5-MO3 / TiO2). x Selective conversion to nitrogen is achieved. However, commercial vanadium-titanium-based SCR catalysts still face challenges such as a narrow reaction temperature window, high SO2 oxidation rate, and susceptibility to poisoning by flue gas impurities. This is especially true in SCR systems located in high-dust zones, where heavy metals (such as As and Pb) carried in the flue gas easily deposit on the catalyst surface, leading to pore blockage, active site coverage, and chemical structure damage, severely reducing catalyst activity and shortening catalyst life. Therefore, developing a denitrification catalyst with high denitrification performance while also resisting heavy metal poisoning is of great significance for the safe and stable operation of SCR systems in coal-fired power plants.
[0003] In recent years, molecular sieves have been widely used as supports or active components for novel denitrification catalysts due to their unique regular pore structure, tunable surface acidity, and excellent hydrothermal stability. Studies have shown that combining molecular sieves with metallic active components can broaden the catalyst's activity temperature window to some extent. For example, Chinese invention patent CN118788378A proposes a modification method for ZSM-5 molecular sieves, which constructs a hierarchical porous structure through alkali treatment and ion exchange, and loads Mn-Ce bimetallic oxides, effectively improving the catalyst's low-temperature activity. However, this method still falls under the category of traditional supported catalysts, with the active component mainly attached to the outer surface and pores of the molecular sieve. Under long-term operation and in heavy metal atmospheres, it still faces the risks of active component detachment, sintering, and pore blockage, and its resistance to heavy metal poisoning is limited.
[0004] In addition, directly introducing the active component into the molecular sieve framework is another improvement approach. Chinese invention patent CN120679597A discloses a hierarchical porous Fe@AFI molecular sieve-type denitration catalyst, which adds iron oxide during hydrothermal synthesis, utilizing its space-occupying effect to induce the formation of intercrystalline mesopores and encapsulate iron species within the molecular sieve framework. While this approach enhances the thermal stability of the active component, its preparation method focuses on controlling the morphology and pore size of the molecular sieve through iron oxide. The final catalyst still requires impregnation to load other active components such as vanadium and copper, making the preparation process relatively complex and not addressing the optimization of its resistance to heavy metal poisoning.
[0005] It is evident that existing molecular sieve-based denitrification catalysts mainly focus on improving intrinsic activity and thermal stability through pore structure optimization or active component dispersion. However, there is still a lack of effective technical means to fundamentally solve the problem of catalyst poisoning in flue gas containing heavy metals (especially arsenic) from the structural design level.
[0006] In view of this, the present invention is proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a denitrification catalyst resistant to heavy metal poisoning and its preparation method. This denitrification catalyst still has high denitrification activity under high arsenic loading, can effectively resist heavy metal poisoning, and solves the problem of denitrification catalyst poisoning and deactivation.
[0008] In a first aspect, the present invention provides a method for preparing a denitrification catalyst resistant to heavy metal poisoning, comprising the following steps: S1. Dissolve aluminum source, silicon source, and phosphorus source in an aqueous solution containing a structure-directing agent, stir evenly, and then add a mesoporous template agent to obtain an initial gel. After hydrothermal crystallization, washing, drying, and calcination, the initial gel is used to obtain SAPO-n molecular sieve. S2. Add SAPO-n molecular sieve to an ethanol solution containing surfactant to obtain mixed solution A; add titanium source, vanadium source, molybdenum source and antimony source precursor to a solution containing surfactant, high molecular weight alcohol and citric acid, stir to dissolve, and obtain mixed solution B. S3. Slowly add mixed solution B to mixed solution A, stir the reaction thoroughly, and then dry and calcine to obtain core-shell type SAPO-n@TiO2-V2O5-MoO3-Sb2O3. S4. Add core-shell type SAPO-n@TiO2-V2O5-MoO3-Sb2O3 to alkaline solution, stir evenly, and then perform alkaline treatment in a reactor to obtain TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with hollow structure.
[0009] In the preparation method of the anti-heavy metal poisoning denitrification catalyst of the present invention, firstly, a hierarchical porous SAPO-n molecular sieve is prepared by the traditional hydrothermal crystallization method with the addition of a mesoporous template agent to reduce the crystallinity of SAPO-n; then, the surface of SAPO-n molecular sieve is modified by adding a surfactant to enable the titanium source, vanadium source, molybdenum source and antimony source to grow better on the surface of SAPO-n molecular sieve and avoid the phenomenon of two-phase separation; finally, the obtained core-shell material is placed in a reactor for high temperature and high pressure alkali treatment. By precisely controlling the concentration, temperature and time of alkali treatment, and taking advantage of the disadvantage of easy collapse and easy dissolution of the crystal structure under high alkali concentration, the core phase SAPO-n molecular sieve is completely removed without the shell layer being affected by alkali treatment, thus obtaining a TiO2-V2O5-MoO3-Sb2O3 denitrification catalyst with a hollow structure. Under high arsenic loading, the optimized design of the hollow structure provides a physical space for heavy metals to be deposited on the inner surface of the shell, thereby effectively delaying the diffusion and coverage of heavy metals to the active sites. This avoids the poisoning and deactivation problems caused by pore blockage or active site coverage in the prior art, and significantly improves the service life of the denitrification catalyst in the environment of heavy metal flue gas.
[0010] As a preferred embodiment of this technical solution, in step S1, the structure directing agent includes any one or more of tetraethylammonium hydroxide, n-propylamine, and isopropylamine, and is preferably n-propylamine; The mesoporous template agent includes any one or more of hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium bromide (DTAB), and trimethoxysilyltrimethylenedimethyloctadecylammonium chloride (TPOAC), and is preferably trimethoxysilyltrimethylenedimethyloctadecylammonium chloride (TPOAC).
[0011] In the molecular sieve preparation process, this invention introduces mesoporous elements into the molecular sieve crystals by adding a mesoporous template agent to reduce the crystallinity of the molecular sieve. This facilitates the complete removal of the core phase SAPO-n molecular sieve from the prepared SAPO-n@TiO2-V2O5-MoO3-Sb2O3 catalytic material under subsequent alkaline conditions, forming a hollow TiO2-V2O5-MoO3-Sb2O3 denitration catalyst.
[0012] More preferably, the aluminum source includes any one of alumina, aluminum isopropoxide, and aluminum sol, and is preferably aluminum isopropoxide; the silicon source includes any one of tetraethyl orthosilicate, silica sol, and silicon dioxide, and is preferably tetraethyl orthosilicate; the phosphorus source includes any one of phosphoric acid, ammonium dihydrogen phosphate, and phosphorus pentoxide, and is preferably phosphoric acid.
[0013] In a preferred embodiment of this technical solution, in step S1, the molar ratio of Al2O3, SiO2, P2O5, structure-directing agent, mesoporous template agent, and water in the initial gel is (0.5-1.7):(0.3-2.1):(0.4-1.5):(0.3-1.2):(0.005-2.7):(70-520), which can also be converted to a molar ratio of Al2O3, SiO2, P2O5, structure-directing agent, mesoporous template agent, and water of 1:(0.176-4.2):(0.235-3.0):(0.176-2.4):(0.0029-5.4):(41.17-1040), wherein the oxide corresponding to the aluminum source is Al2O3, the oxide corresponding to the silicon source is SiO2, and the oxide corresponding to the phosphorus source is P2O5.
[0014] More preferably, the molar ratio of Al2O3, SiO2, P2O5, structure directing agent, mesoporous template agent and water is 1:(0.9-2.24):(1.74-2.79):(1.09-1.846):(0.004-0.1):(511-1023).
[0015] Further preferably, the molar ratio of Al2O3, SiO2, P2O5, structure directing agent, mesoporous template agent and water is 1:0.6:1:0.3:0.005:500.
[0016] As a preferred embodiment of this technical solution, in step S1, during the hydrothermal crystallization, the sample is transferred to a stainless steel hydrothermal reactor for crystallization, and the temperature is controlled at 160-200℃ for 36-72 hours.
[0017] More preferably, the crystallized sample is washed until neutral, dried at 85°C overnight, and calcined at 500°C for 6 hours to obtain SAPO-n molecular sieve. The present invention does not strictly limit the specific conditions for drying and calcination.
[0018] More preferably, the SAPO-n molecular sieve prepared by the present invention is any one of SAPO-34, SAPO-5 and SAPO-41.
[0019] As a preferred embodiment of this technical solution, in step S2, the mass ratio of SAPO-n molecular sieve, surfactant and ethanol in the mixed solution A is 1:(0.1-0.5):(1-15), and preferably 1:(0.1-0.35):(4-8).
[0020] In the mixed solution B, the mass ratio of the titanium source (calculated as titanium dioxide) to the surfactant, polymeric alcohol and citric acid is 1:(0.1-0.5):(0.01-1):(0.01-0.3), and preferably 1:(0.15-0.5):(0.15-0.25):(0.02-0.6).
[0021] As a preferred embodiment of this technical solution, in step S2, the surfactant includes any one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), polyoxyethylene-polypropylene oxide block copolymer (F127), and sodium dodecylbenzenesulfonate (SDS), and is preferably polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).
[0022] The polymeric alcohol includes any one or more of polyethylene glycol 1000 (PEG1000), polyethylene glycol 2000 (PEG2000) and polyethylene glycol 5000 (PEG5000), and is preferably polyethylene glycol 5000 (PEG5000).
[0023] In a preferred embodiment of this technical solution, in step S2, the titanium source includes any one of titanium isopropoxide, tetraethyl titanate, and titanium n-butoxide, and is preferably titanium isopropoxide; the vanadium source includes any one of ammonium metavanadate, vanadium oxalate, and vanadium oxalate, and is preferably ammonium metavanadate; the molybdenum source includes any one of ammonium dimolybdate, ammonium tetramolybdate, and ammonium heptamolybdate, and is preferably ammonium heptamolybdate; the antimony source includes any one of antimony oxide, antimony acetate, and antimony glycolate, and is preferably antimony acetate.
[0024] As a preferred embodiment of this technical solution, in step S3, the stirring reaction is carried out at a temperature of 40-80℃ for 2-4 hours.
[0025] As a preferred embodiment of this technical solution, in step S4, the mass ratio of the core-shell type SAPO-n@TiO2-V2O5-MoO3-Sb2O3 to the alkaline solution is 1:(1-5).
[0026] More preferably, the concentration of the alkaline solution is 0.01-2 mol / L; More preferably, the alkaline solution includes any one or more of sodium hydroxide, potassium hydroxide, and sodium carbonate, and is preferably sodium hydroxide.
[0027] In a preferred embodiment of this technical solution, during step S4, the alkali treatment is carried out at a temperature of 90-140℃ for a duration of 4-24 hours.
[0028] Secondly, the present invention also discloses an anti-heavy metal poisoning denitrification catalyst prepared by the above preparation method, which should also fall within the protection scope of the present invention.
[0029] In a preferred embodiment of this technical solution, the loading of V2O5 in the denitrification catalyst is 1wt%-3wt%, the loading of MoO3 is 2wt%-5wt%, and the loading of Sb2O3 is 1wt%-3wt%. However, this invention does not strictly limit the loading of V2O5, MoO3, and Sb2O3, but rather aims to achieve the best results.
[0030] The preparation method of the anti-heavy metal poisoning denitration catalyst of the present invention has at least the following beneficial effects: 1. This invention uses hierarchical porous SAPO-n molecular sieves as sacrificial templates, taking advantage of their tendency to collapse and dissolve easily under high alkali concentrations. A TiO2-V2O5-MoO3-Sb2O3 composite shell is constructed on its surface, followed by a precise alkali treatment process to completely remove the internal SAPO-n molecular sieve cores, ultimately yielding a hollow TiO2-V2O5-MoO3-Sb2O3 denitration catalyst. This hollow structure provides physical space for heavy metals, allowing them to deposit on the inner surface of the shell, effectively delaying the diffusion and coverage of heavy metals to active sites. This avoids the poisoning and deactivation problems caused by pore blockage or active site coverage in existing technologies, significantly improving the service life of the denitration catalyst in environments containing heavy metal flue gas. This denitration catalyst has high industrial value in high-arsenic coal used in coal-fired power plants.
[0031] 2. This invention introduces surfactants to modify the interface of the hierarchical porous SAPO-n molecular sieve surface, optimizing its physicochemical properties and ensuring good interfacial compatibility with titanium, vanadium, molybdenum, and antimony source precursors. This drives the uniform growth of active component precursors on the SAPO-n molecular sieve surface. This solves the problems of active component agglomeration and weak bonding with the support in traditional loading methods, avoids the reduction of active sites and catalytic efficiency caused by phase separation, and ensures the integrity and structural stability of the shell.
[0032] 3. In the hollow TiO2-V2O5-MoO3-Sb2O3 catalytic material prepared in this invention, V2O5 serves as the main active component to provide denitrification activity, MoO3 acts as an additive to improve thermal stability and sulfur resistance, and Sb2O3 is used to further modulate surface acidity and redox capabilities. The synergistic effect of multiple components endows the denitrification catalyst with a wide activity temperature window and high denitrification efficiency. Simultaneously, the high specific surface area resulting from the hollow structure facilitates the adsorption and diffusion of reactant molecules, further enhancing the catalytic reaction efficiency and overcoming the shortcomings of traditional vanadium-titanium-based catalysts, such as easy deactivation at high temperatures and a narrow activity temperature window.
[0033] 4. In the preparation process, the Al, Si, and P components dissolved by the core phase SAPO-n molecular sieve under alkaline conditions are recovered and reused. They can continue to be used as Al, Si, and P sources required for the synthesis of SAPO-n molecular sieve, which further improves the utilization rate of raw materials and reduces production costs, thus realizing the resource utilization of waste liquid.
[0034] 5. The preparation method of the anti-heavy metal poisoning denitration catalyst of the present invention has relatively mild reaction conditions, good reproducibility, simple process, and all raw materials for synthesis are from industrial products, which are inexpensive and readily available, and have broad prospects for industrial application. Attached Figure Description
[0035] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0036] Figure 1 XRD pattern of the anti-heavy metal poisoning denitrification catalyst obtained in Example 1 of this invention; Figure 2 This is a SEM image of the nucleated SAPO-34 molecular sieve obtained in Example 1 of the present invention; Figure 3 This is a SEM image of the core-shell catalytic material SAPO-34@TiO2-V2O5-MoO3-Sb2O3 obtained in Example 1 of this invention; Figure 4 This is a SEM image of the TiO2-V2O5-MoO3-Sb2O3 denitrification catalyst with a hollow structure in Example 1 of the present invention after being subjected to extrusion and crushing treatment; Figure 5 This is a comparison chart of the denitrification performance of the denitrification catalyst TiO2-V2O5-MoO3-Sb2O3 in Example 1 and the denitrification catalyst TiO2 / V2O5-MoO3-Sb2O3 in Control Example 1 of the present invention; Figure 6 This is a comparison chart of the arsenic resistance performance of the denitrification catalyst TiO2-V2O5-MoO3-Sb2O3 in Example 1 and the denitrification catalyst TiO2 / V2O5-MoO3-Sb2O3 in Control Example 1. Detailed Implementation
[0037] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0038] It should be noted that the terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the exemplary implementations according to this application. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this description, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0039] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Example 1 S11. Weigh 6g of aluminum isopropoxide and dissolve it in a mixture of 140mL distilled water and 0.95g of n-propylamine. Stir until completely dissolved. Then, add 3.3g of silica sol (30wt.%), 3.5mL of phosphoric acid, and 0.3g of CTAB in sequence. Stir until homogeneous to obtain an initial gel. Transfer the initial gel to a stainless steel hydrothermal reactor for crystallization at 165℃ for 45h. Wash the crystallized sample until neutral, dry it overnight at 85℃, and calcine it at 500℃ for 6h to obtain SAPO-34 molecular sieve. S12. Take 1g of the SAPO-34 molecular sieve powder obtained above and add it to a solution containing 0.1g P123 and 5mL of ethanol to obtain mixed solution A; take 20g of isopropyl titanate, 0.15g of ammonium metavanadate, 0.13g of ammonium heptamolybdate and 0.11g of antimony acetate and add them to a solution containing 1g P123, 1g of polyethylene glycol 1000 and 0.15g of citric acid, stir thoroughly to dissolve, and obtain mixed solution B; S13. At a water bath temperature of 40°C, the above mixed solution B was slowly added dropwise to mixed solution A. After thorough stirring, it was dried at 85°C for 12 hours and then calcined at 550°C for 6 hours to obtain the core-shell type SAPO-34@TiO2-V2O5-MoO3-Sb2O3 catalytic material. S14. Take 1g of the above-obtained catalyst material and add it to 1g of a 0.01mol / L sodium hydroxide solution. After stirring evenly, put it into a reaction vessel and treat it at 120℃ for 12h to obtain a TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure.
[0041] Example 2 S21. Weigh 1.1g of pseudoboehmite and dissolve it in a mixture of 165mL distilled water and 1.0g of n-propylamine. Stir until completely dissolved. Then, add 4.1g of silica sol (30wt.%), 3.5mL of phosphoric acid, and 0.35g of CTAB in sequence. Stir until homogeneous to obtain the initial gel. Transfer the initial gel to a stainless steel hydrothermal reactor for crystallization at 175℃ for 40h. Wash the crystallized sample until neutral, dry it overnight at 85℃, and calcine it at 500℃ for 6h to obtain SAPO-5 molecular sieve. S22. Take 1g of the SAPO-5 molecular sieve powder obtained above and add it to a solution containing 0.2g P123 and 6mL of ethanol to obtain mixed solution A; take 18g of isopropyl titanate, 0.13g of ammonium metavanadate, 0.12g of ammonium heptamolybdate and 0.08g of antimony acetate and add them to a solution containing 2.5g F127, 1.3g of polyethylene glycol 2000 and 0.3g of citric acid, stir thoroughly to dissolve, and obtain mixed solution B; S23. At a water bath temperature of 45℃, mixed solution B was slowly added dropwise to mixed solution A. After thorough stirring, the mixture was dried at 85℃ for 12 hours and then calcined at 550℃ for 6 hours to obtain a core-shell type SAPO-5@TiO2-V2O5-MoO3-Sb2O3 catalytic material. S24. Take 1g of the above-obtained catalyst material and add it to 2.5g of 0.03mol / L sodium hydroxide solution. After stirring evenly, put it into a reaction vessel and treat it at 130℃ for 12h to obtain a TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure.
[0042] Example 3 This embodiment is basically the same as Embodiment 1, except that: P123 in step S12 of Embodiment 1 is replaced with F127; sodium hydroxide in step S15 is replaced with potassium hydroxide, and other conditions remain unchanged.
[0043] Example 4 This embodiment is basically the same as Embodiment 2, except that: in step S23 of Embodiment 2, 1.3g of polyethylene glycol 2000 is replaced with 1.3g of polyethylene glycol 1000, while other conditions remain unchanged.
[0044] Example 5 S51. Weigh 5.9g of aluminum isopropoxide and dissolve it in a mixture of 160mL distilled water and 1.15g of isopropylamine. Stir until completely dissolved. Then, add 0.9g of fumed SiO2, 4.1mL of phosphoric acid, and 0.33g of P123 in sequence. Stir until homogeneous to obtain an initial gel. Transfer the initial gel to a stainless steel hydrothermal reactor for crystallization at 180℃ for 50h. Wash the crystallized sample until neutral, dry it overnight at 85℃, and calcine it at 500℃ for 6h to obtain SAPO-37 molecular sieve. S52. Take 1g of the SAPO-37 molecular sieve powder obtained above and add it to a solution containing 0.35g F127 and 10mL of ethanol to obtain mixed solution A; take 23.5g of isopropyl titanate, 0.17g of ammonium metavanadate, 0.1g of ammonium heptamolybdate and 0.23g of antimony acetate and add them to a solution containing 1g F127, 0.85g of polyethylene glycol 1000 and 0.14g of citric acid, stir thoroughly to dissolve, and obtain mixed solution B; S53. At a water bath temperature of 40℃, mixed solution B was slowly added dropwise to mixed solution A. After thorough stirring, the mixture was dried at 85℃ for 12 hours and then calcined at 550℃ for 6 hours to obtain a core-shell type SAPO-37@TiO2-V2O5-MoO3-Sb2O3 catalytic material. S54. Take 1g of the above-obtained catalyst material and add it to 5g of 0.01mol / L sodium hydroxide solution. After stirring evenly, put it into a reaction vessel and treat it at 120℃ for 12h to obtain a TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure.
[0045] Example 6 S61. Weigh 1.5g of alumina and dissolve it in a mixture of 150mL distilled water and 1.5g of isopropylamine. Stir until completely dissolved. Then add 3.0g of silica sol (30wt%), 3.8mL of phosphoric acid, and 1.3g of F127 in sequence. After stirring evenly, an initial gel is obtained. Transfer the initial gel to a stainless steel hydrothermal reactor for crystallization at 170℃ for 48h. Wash the crystallized sample until neutral, dry it overnight at 85℃, and calcine it at 500℃ for 6h to obtain SAPO-34 molecular sieve. S62. Take 1g of the SAPO-34 molecular sieve powder obtained above and add it to a solution containing 0.1g F127 and 8mL of ethanol to obtain mixed solution A; take 15g of isopropyl titanate, 1g of vanadium oxalate, 0.12g of ammonium heptamolybdate and 0.16g of antimony acetate and add them to a solution containing 2.0g P123, 1g of polyethylene glycol 1000 and 0.23g of citric acid, stir thoroughly to dissolve, and obtain mixed solution B; S63. At a water bath temperature of 40℃, mixed solution B was slowly added dropwise to mixed solution A. After thorough stirring, the mixture was dried at 85℃ for 12 hours and then calcined at 550℃ for 6 hours to obtain a core-shell type SAPO-34@TiO2-V2O5-MoO3-Sb2O3 catalytic material. S64. Take 1g of the above-obtained catalyst material and add it to 3.5g of 0.1mol / L potassium hydroxide solution. After stirring evenly, put it into a reaction vessel and treat it at 120℃ for 12h to obtain a TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure.
[0046] Example 7 S71. Weigh 1.7g of alumina and dissolve it in a mixture of 150mL distilled water and 1.5g of isopropylamine. Stir until completely dissolved. Then add 3.0g of silica sol (30wt%), 4.5mL of phosphoric acid, and 0.42g of P123 in sequence. Stir until homogeneous to obtain an initial gel. Transfer the initial gel to a stainless steel hydrothermal reactor for crystallization at 170℃ for 48h. Wash the crystallized sample until neutral, dry it overnight at 80℃, and calcine it at 500℃ for 6h to obtain SAPO-34 molecular sieve. S72. Take 1g of the SAPO-34 molecular sieve powder obtained above and add it to a solution containing 0.13g F127 and 8mL of ethanol to obtain mixed solution A; take 23.5g of isopropyl titanate, 1g of vanadium oxalate, 0.12g of ammonium heptamolybdate and 0.16g of antimony acetate and add them to a solution containing 3g P123, 1g of polyethylene glycol 1000 and 0.23g of citric acid, stir thoroughly to dissolve, and obtain mixed solution B; S73. At a water bath temperature of 45℃, mixed solution B was slowly added dropwise to mixed solution A. After thorough stirring, the mixture was dried at 90℃ for 12 hours and then calcined at 500℃ for 6 hours to obtain a core-shell type SAPO-34@TiO2-V2O5-MoO3-Sb2O3 catalytic material. S74. Take 1g of the above-obtained catalyst material and add it to 4.7g of 0.1mol / L potassium hydroxide solution. After stirring evenly, put it into a reaction vessel and treat it at 120℃ for 12h to obtain a TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure.
[0047] Compare with Example 1 5.6g of commercially available TiO2 was weighed and impregnated into a solution containing 0.15g ammonium metavanadate, 0.13g ammonium heptamolybdate, and 0.11g antimony acetate. Before use, ammonium heptamolybdate and antimony acetate were added to 25g distilled water containing 0.1g P123, 1g polyethylene glycol 1000, and 0.15g citric acid, and stirred thoroughly to promote solvent absorption. After impregnation, the solution was dried at 120℃ for 48h and then calcined at 550℃ for 8h to obtain a supported TiO2 / V2O5-MoO3-Sb2O3 denitration catalyst.
[0048] Compare with Example 2 This comparative example is basically the same as Example 1, except that P123 mesoporous template agent was not added during the preparation of SAPO-34 molecular sieve in step S11.
[0049] Compare with Example 3 This comparative example is basically the same as Example 1, except that: in the process of preparing mixed solution A in step S12, surfactant P123 was not added.
[0050] Compare with Example 4 This comparative example is basically the same as Example 1, except that: in step S14, during the alkali treatment, 1g of the above-obtained catalyst material was added to 1g of a 0.001mol / L sodium hydroxide solution.
[0051] Figure 1 The XRD pattern is shown for the hollow TiO2-V2O5-MoO3-Sb2O3 denitration catalyst prepared in Example 1 of this invention.
[0052] Depend on Figure 1 As can be seen from step S11, only the characteristic diffraction peaks of SAPO-34 were detected in the sample synthesized, indicating that no other impurities were formed. After processing in step S13, from... Figure 1 It can be clearly observed that, in addition to the characteristic diffraction peaks of SAPO-34, characteristic diffraction peaks of anatase TiO2 also appear, but the characteristic diffraction peaks of the active components V2O5, MoO3, and Sb2O3 are not present, indicating that these active components are highly dispersed on the support surface. Furthermore, this further demonstrates the successful synthesis of the SAPO-34@TiO2-V2O5-MoO3-Sb2O3 catalytic material. After treatment in step S14, the characteristic diffraction peaks of SAPO-34 completely disappear, and the crystallinity of TiO2 remains good. Figure 1 c) indicates that the nucleus phase SAPO-34 molecular sieve has been completely removed.
[0053] Figure 2 and Figure 3The images show SEM images of the core-phase SAPO-34 molecular sieve and the core-shell SAPO-34@TiO2-V2O5-MoO3-Sb2O3 catalytic material obtained in Example 1 of this invention.
[0054] Based on the SEM images, it can be seen that the synthesized SAPO-34 is a spherical aggregate formed by the stacking of nanocrystals. Figure 2 After depositing a layer of TiO2-V2O5-MoO3-Sb2O3, its surface is relatively smooth. Figure 3 The XRD pattern further demonstrates that the present invention successfully synthesized a core-shell type SAPO-34@TiO2-V2O5-MoO3-Sb2O3 catalytic material.
[0055] Figure 4 The image shows a SEM image of the TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure prepared in Example 1 of this invention after being crushed by extrusion.
[0056] Depend on Figure 4 As can be seen from the electron microscope image, the sample obtained after the alkali treatment in step S14, after being crushed, has a spherical morphology with a hollow interior. The core SAPO-34 is completely removed, while the shell structure remains intact. This indicates that the present invention has successfully prepared a TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with a hollow structure.
[0057] This invention further investigated the catalytic performance and poisoning resistance of the denitration catalysts in Examples 1-7 and Control Examples 1-4. The specific experimental methods are as follows: Arsenic poisoning of denitration catalysts was investigated using a simulated poisoning method, as detailed below: The denitrification catalyst was passed through a 20-40 mesh sieve, and the catalyst powder was weighed and placed in a tube furnace. A certain amount of As₂O₃ was placed at the front end of the denitrification catalyst. N₂ containing 3 vol% H₂O was introduced into the tube furnace, and the temperature was raised to 350°C. As₂O₃ vapor was loaded onto the denitrification catalyst with the gas flow. Subsequently, the denitrification catalyst was treated at 370°C for 10 hours in an N₂ atmosphere containing 3 vol% O₂ to obtain a denitrification catalyst simulating arsenic poisoning. Chemical composition analysis showed that the As₂O₃ loading was 4.5 wt%.
[0058] Furthermore, the denitrification performance of the denitrification catalyst after arsenic poisoning was tested in a micro fixed-bed reactor under atmospheric pressure. The denitrification catalyst loading was 0.3 g, and a mixture of NO, NH3, O2, and N2 was used to simulate industrial flue gas. The volume fractions of NO, NH3, and O2 were 0.05%, 0.05%, and 5%, respectively, with N2 used as the balance gas. The flow rate of the mixed gas was 1 L / min. The volume fractions of NO and NO2 in the mixed gas after the reaction were analyzed using a GA-21plus flue gas analyzer (Madur GmbH, Austria), and the denitrification efficiency ηNO (%) was calculated using the following formula. The denitrification efficiency of the denitrification catalyst at different temperatures was obtained using this formula, and the results are detailed in Table 1.
[0059] ηNO (%) = ([NO] in -[NO] out -[NO2] out ) / [NO] in ×100% Table 1. Denitrification efficiency of denitrification catalysts at different temperatures.
[0060] As shown in Table 1, the denitrification catalysts prepared in Examples 1-7 of this invention have a wider activity temperature window and higher denitrification efficiency compared to traditional denitrification catalysts and catalysts in other comparative examples. In Comparative Example 2, no mesoporous template agent was added during the preparation of SAPO-34, resulting in a smaller pore size of the prepared molecular sieve. During subsequent shell coating of the active component, the active component precursor had difficulty penetrating deep into the pores and mostly accumulated on the outer surface of the particles, leading to weak bonding between the shell and the molecular sieve core and uneven coating. During alkali treatment for denucleation, the weak shell was prone to cracking or detachment, failing to form a complete and robust hollow structure, resulting in poor catalytic activity and stability of the final product. In Comparative Example 3, no surfactant was added during the preparation of mixed solution A. The surface charge and properties of the SAPO-34 molecular sieve in the ethanol solution were not optimized, resulting in the inability of the metal precursor to be uniformly adsorbed and grown on the molecular sieve surface. After alkali treatment, a hollow structure could not be formed, or only a broken and incomplete shell could be formed, making it difficult to guarantee the activity and stability of the catalyst. In Comparative Example 4, the excessively low concentration of alkali solution prevented the SAPO molecular sieve from being effectively removed, and the catalyst lost the cavity used to contain heavy metals, resulting in poor resistance to poisoning.
[0061] Figure 5The figure shows the denitrification performance of the denitrification catalyst obtained in Example 1. As can be seen from the figure, the denitrification activity of the hollow TiO2-V2O5-MoO3-Sb2O3 denitrification catalyst obtained by the preparation method of the present invention is higher than that of the conventional TiO2 / V2O5-MoO3-Sb2O3 catalyst (Control Example 1) in the entire temperature range (200-420℃), especially in the low temperature range where the denitrification activity is significantly improved.
[0062] Figure 6 The catalytic performance of the denitration catalyst was simulated after arsenic poisoning. Compared with the fresh denitration catalyst without simulated poisoning, although the denitration activity of both was reduced, the conventional TiO2 / V2O5-MoO3-Sb2O3 showed more severe deactivation. For example, at a reaction temperature of 290℃, the activity of the arsenic-loaded TiO2 / V2O5-MoO3-Sb2O3 denitration catalyst decreased by 14.8%, while the denitration activity of the hollow-structured TiO2-V2O5-MoO3-Sb2O3 denitration catalyst of this invention decreased by only 4.2%. This fully demonstrates that the hollow-structured TiO2-V2O5-MoO3-Sb2O3 denitration catalyst of this invention has a strong capacity to accommodate arsenic, effectively preventing deactivation due to poisoning and improving the arsenic poisoning resistance of the denitration catalyst.
[0063] In summary, this invention combines the easy removal characteristics of molecular sieves with the catalytic activity of composite oxides. It utilizes the internal cavity of the hollow structure to provide physical space for heavy metals such as arsenic, effectively delaying the poisoning and deactivation of active sites. This fundamentally solves the technical problem that traditional supported catalysts are prone to deactivation due to pore blockage and active site coverage in environments containing heavy metal flue gas, achieving both high denitrification efficiency and excellent resistance to heavy metal poisoning.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a denitrification catalyst resistant to heavy metal poisoning, characterized in that, Includes the following steps: S1. Dissolve aluminum source, silicon source, and phosphorus source in an aqueous solution containing a structure-directing agent, stir evenly, and then add a mesoporous template agent to obtain an initial gel. After hydrothermal crystallization, washing, drying, and calcination, the initial gel is used to obtain SAPO-n molecular sieve. S2. Add SAPO-n molecular sieve to an ethanol solution containing surfactant to obtain mixed solution A; add titanium source, vanadium source, molybdenum source and antimony source precursor to a solution containing surfactant, high molecular weight alcohol and citric acid, stir to dissolve, and obtain mixed solution B. S3. Slowly add mixed solution B to mixed solution A, stir the reaction thoroughly, and then dry and calcine to obtain core-shell type SAPO-n@TiO2-V2O5-MoO3-Sb2O3. S4. Add core-shell type SAPO-n@TiO2-V2O5-MoO3-Sb2O3 to alkaline solution, stir evenly, and then perform alkaline treatment in a reactor to obtain TiO2-V2O5-MoO3-Sb2O3 denitration catalyst with hollow structure.
2. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S1, the structure directing agent includes any one or more of tetraethylammonium hydroxide, n-propylamine, and isopropylamine; The mesoporous template agent includes any one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, and trimethoxysilyltrimethylenedimethyloctadecylammonium chloride.
3. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S1, the molar ratio of Al2O3, SiO2, P2O5, structure directing agent, mesoporous template agent and water in the initial gel is (0.5-1.7):(0.3-2.1):(0.4-1.5):(0.3-1.2):(0.005-2.7):(70-520).
4. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S1, during the hydrothermal crystallization, the temperature is controlled at 160-200℃ and the time is 36-72h.
5. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S2, the mass ratio of SAPO-n molecular sieve, surfactant, and ethanol in the mixed solution A is 1:(0.1-0.5):(1-15). In the mixed solution B, the mass ratio of the titanium source (calculated as titanium dioxide) to the surfactant, polymeric alcohol, citric acid and water is 1:(0.1-0.5):(0.01-1):(0.01-0.3):(1-5).
6. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S2, the surfactant includes any one or more of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polyethylene oxide-polypropylene oxide block copolymer, and sodium dodecylbenzenesulfonate. The high molecular weight alcohol includes any one or more of polyethylene glycol 1000, polyethylene glycol 2000, and polyethylene glycol 5000.
7. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S3, the stirring reaction is carried out at a temperature of 40-80℃ for 2-4 hours.
8. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S4, the mass ratio of the core-shell type SAPO-n@TiO2-V2O5-MoO3-Sb2O3 to the alkaline solution is 1:(1-5). Preferably, the concentration of the alkaline solution is 0.01-2 mol / L; Preferably, the alkaline solution comprises any one or more of sodium hydroxide, potassium hydroxide, and sodium carbonate.
9. The preparation method of the anti-heavy metal poisoning denitration catalyst according to claim 1, characterized in that, In step S4, the alkali treatment is carried out at a temperature of 90-140℃ for 4-24 hours.
10. A denitrification catalyst resistant to heavy metal poisoning, characterized in that, The catalyst for denitrification against heavy metal poisoning is prepared according to any one of claims 1-9.
Citation Information
Patent Citations
Modified molecular sieve denitration catalyst as well as preparation method and application thereof
CN118788378A
Hierarchical pore Fe-AFI molecular sieve type denitration catalyst and preparation method thereof
CN120679597A
